Ultrafast Elemental and Oxidation-State Mapping of Hematite by 4D Electron Microscopy - Su, Zixue; Baskin, J Spencer; Zhou, Wuzong; Thomas, John M; Zewail, Ahmed H (Journal of the American Chemical Society, 2017)
We describe a new methodology that sheds light on the fundamental electronic processes that occur at the subsurface regions of inorganic solid photocatalysts. Three distinct kinds of microscopic imaging are used that yield spatial, temporal, and energy-resolved information. We also carefully consider the effect of photon-induced near-field electron microscopy (PINEM), first reported by Zewail et al. in 2009. The value of this methodology is illustrated by studying afresh a popular and viable photocatalyst, hematite, α-Fe O that exhibits most of the properties required in a practical application. By employing high-energy electron-loss signals (of several hundred eV), coupled to femtosecond temporal resolution as well as ultrafast energy-filtered transmission electron microscopy in 4D, we have, inter alia, identified Fe ions that have a lifetime of a few picoseconds, as well as associated photoinduced electronic transitions and charge transfer processes.